2018
DOI: 10.1017/s0263574718000991
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral and gaze data fusion for wheelchair navigation enhancement: case of distracted users

Abstract: SUMMARYThe goal of this paper is to present a new hybrid system based on the fusion of gaze data and Steady State Visual Evoked Potentials (SSVEP) not only to command a powered wheelchair, but also to account for users distraction levels (concentrated or distracted). For this purpose, a multi-layer perception neural network was set up in order to combine relevant gazing and blinking features from gaze sequence and brainwave features from occipital and parietal brain regions. The motivation behind this work is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Authors in [76] successfully linked visible feedback using a combination of Emotiv and a head-mounted device named HTC VIVE to familiarize disabled people with brain-machine interaction on a 3-D space. In two separate studies, Lamti et al developed EEG and gaze data fusing framework for wheelchair navigation [77] and, in [88], Emotiv and a Tobii eye tracker (EyeX model) that were were used to monitor brain and eye activities.…”
Section: Brain-computer Interfacementioning
confidence: 99%
“…Authors in [76] successfully linked visible feedback using a combination of Emotiv and a head-mounted device named HTC VIVE to familiarize disabled people with brain-machine interaction on a 3-D space. In two separate studies, Lamti et al developed EEG and gaze data fusing framework for wheelchair navigation [77] and, in [88], Emotiv and a Tobii eye tracker (EyeX model) that were were used to monitor brain and eye activities.…”
Section: Brain-computer Interfacementioning
confidence: 99%
“…TMSI benefits from exploiting the temporally local structure of EEG signals and could be a potential method for the performance of SSVEP-based BCI. In our former study (Lamti et al 2018), an active gaze/SSVEP hybrid wheelchair command system was set up in order to enhance navigation performance. This project deals mainly with the case of distracted users where gaze and cerebral distractions were added.…”
Section: Ssvepmentioning
confidence: 99%
“…The conclusions will be exploited as a basis for future schemes in order to ensure the migration of those findings from simulation to real life situations. Speaking of which, in our former studies, P300 and SSVEP were used as a source of control for wheelchair commands (more details could be found in Lamti et al 2016Lamti et al , 2018 (as part of active BCI systems). In an inverse scheme, under the framework of passive BCI, those same modalities are assessed in order to detect, estimate and predict the user's state (mental fatigue and emotions).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that deeper investigations could detect efficiently the introduction of the time pressure factor as stressor. In our previous work [ 26 , 27 ] time pressure was investigated as stressor as well as its influence on EEG data. It was concluded that temporal and frequency features extracted from frontal and fronto-central sensors were significantly correlated with stress levels.…”
Section: Introductionmentioning
confidence: 99%